Anchoring from shipping as a disturbance agent to temperate rocky reef fish: marked shifts observed in trophic and taxonomic guilds - Broad, Allison; Rees, Matthew J.; Ingleton, Timothy C.; Morris, Bradley; Davis, Andrew R. (Frontiers in Conservation Science, 2025)
Anchoring impacts to marine environments from large, ocean-going ships is increasingly recognized as a global threat to marine biota. To date, no replicated assessment examining anchor disturbance to fish assemblages exists at the scale of ocean-going vessels. Here we aim to fill this important knowledge gap, using the Port Kembla Anchorage in SE Australia as a case study. We predicted that demersal fish on temperate rocky reefs (>30m) exposed to anchoring activities would differ significantly to those that were ‘anchor-free’. Using Baited Remote Underwater Video (BRUV) we assessed species and functional groups using a full-subsets generalized additive mixed modelling approach, including fine-scale reef variables as covariates to account for natural spatial variability and to improve estimates. Reefs exposed to anchoring (ie. disturbed) was the most important predictor for the total abundance of fish, with twice as many individuals when compared to undisturbed reefs (anchor-free). Abundance measures were largely driven by the shoaling zooplanktivore; Atypichthys strigatus, with near four-fold increases of this trophic group on anchored reefs. In contrast, the abundance of other taxa including, Meuschenia freycineti and demersal elasmobranchs combined decreased two to three-fold on disturbed reefs. These results indicate anchoring activities can have ecosystem-wide impacts to fish assemblages underscoring the importance of better managing anchoring near ports globally.